Analisis Orang Dengan HIV (ODHIV) Baru Terdiagnosa di Provinsi Jakarta Tahun 2023 - Rahmat Aji Pramono; Dumilah Ayuningtyas (Journal of Mandalika Literature, 2024)
Abstract contains a brief description of the research objectives, methods used, instruments, data analysis techniques, and research results. The emphasis of writing abstracts is mainly on research results. Abstracts are written in Indonesian and English. Abstract typing is done single-spaced with margins that are narrower than the right and left margins of the main text. Keywords need to be included to describe the realm of the problem under study and the main terms that underlie the implementation of the research. Key words can be single words or a combination of words. The number of key words 3-5 words. These key words are necessary for computerization. Searching for research titles and abstracts is made easier with these key words. HIV disease is a public health problem in Indonesia, there are an estimated 526,841 people with HIV, and the epidemic is concentrated in certain populations (key populations) such as female sex workers, men who have sex with men, transgender women, and injecting drug users. The HIV disease control program in the form of early detection and immediate treatment aims to prevent people with HIV from transmitting it to others. The implementation of the program is recorded and reported through the Sistem Informasi HIV AIDS (SIHA). The purpose of this study was to determine the description of the epidemic of people with HIV who were newly diagnosed in 2023 in Jakarta Province by analyzing SIHA data at the Jakarta Provincial Health Office. The method used is a retrospective descriptive analysis of SIHA data with variables of gender, age, population type, and district. The results of the study showed that people with HIV who were newly diagnosed in 2023 in Jakarta Province were 5,482 people with HIV newly diagnosed, the majority of whom were men aged 26-35 years with a population of MSM. Therefore, it is necessary to implement a massive prevention strategy in this population to further optimize the HIV control program in Jakarta Province.